Health inequalities based on ethnicity in individuals aged 15 to 64, Brazil, 1998 Desigualdades de saúde segundo cor em pessoas de 15 a 64 anos de idade no Brasil, 1998 - Rita Barradas Barata; Márcia Furquim de Almeida; Cláudia Valencia Montero; Zilda Pereira da Silva (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
This study aimed to analyze inequalities in health status and utilization of medical consultations and hospital services by Brazilian young and adult populations according to ethnicity. The survey analyzes a representative sample of the Brazilian population aged 15 to 64 years, except those living in the rural area of the Amazon. The prevalence of fair or poor health status was substantially higher among black men, white women, and black women. The influence of gender and ethnicity remains significant after adjusting for age and socioeconomic conditions (OR = 1.11; 1.49 and 1.86 respectively). Differences between blacks and whites decrease with age, but increase with socioeconomic status. There were 10% more medical consultations among white individuals. The differences were more striking among young people who reported good health status. For individuals with fair or poor health, no differences were observed in frequency of medical consultations between blacks and whites. There were no significant differences in hospitalization rates. With regard to health status, differences between blacks and whites were striking. However, the same was not true for utilization of health services. O objetivo foi analisar desigualdades no estado de saúde, uso de consultas médicas e internações hospitalares na população de jovens e adultos brasileiros segundo cor utilizando dados do suplemento saúde da PNAD 1998, inquérito domiciliar em amostra representativa da população brasileira de 15 a 64 anos, exceto aqueles residentes na Amazônia rural. A prevalência de estado de saúde regular ou ruim foi mais alta entre homens e mulheres negros e mulheres brancas. A influência do gênero e da cor permanece significante após ajustamento por idade e condições sócio-econômicas. As diferenças entre brancos e negros diminuem com a idade e aumentam com o nível sócio-econômico. A freqüência de consultas médicas foi 10% maior entre os brancos. As diferenças são mais notáveis entre os jovens que referem bom estado de saúde. Não há diferença significante nas taxas de hospitalização. Em relação ao estado de saúde, as diferenças entre brancos e negros são marcantes. Entretanto, o mesmo não se observa para a utilização dos serviços de saúde.